Biochemically degradable phosphorus-free nitrogen-free scale inhibitor

By developing a biochemically degradable phosphorus-free nitrogen-free scale inhibitor, using a combination of a variety of polymers and organic acids to form hydrogen bonds, electrostatic interactions and supramolecular structures, the problem of difficult degradation of traditional scale inhibitors is solved, and the dual goals of efficient scale inhibition and environmental protection are achieved.

CN119660978AActive Publication Date: 2025-03-21DALIAN YUTIAN ENVIRONMENTAL PROTECTION TECHCO
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510013530.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-03-21
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

Traditional chemical scale inhibitors are difficult to degrade, resulting in secondary environmental pollution and cannot effectively solve the scale problem in industrial equipment and pipelines.

Method used

A biochemically degradable phosphorus-free nitrogen-free scale inhibitor is developed to form hydrogen bonds, electrostatic interactions and supramolecular structures through the combination of chitosan grafting acrylic copolymer, polyaspartic acid, gluconolactone, potassium citrate, propyl gallate, sodium lactate, polylysine and polycyclohexanedicarboxylic acid, to form hydrogen bonds, electrostatic interactions and supramolecular structures, enhancing scale inhibition and dispersion properties.

Benefits of technology

It achieves efficient degradation of scale inhibitors, improves scale inhibition performance, dispersion performance, thermal stability, shear resistance and service life, while maintaining good biodegradability and environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660978A_ABST
    Figure CN119660978A_ABST
Patent Text Reader

Abstract

The invention relates to the field of scale inhibitors, and discloses a biochemically degradable phosphorus-free and nitrogen-free scale inhibitor. Comprising the following raw materials in parts by weight: 25-35 parts of a chitosan grafted acrylic acid copolymer, 8-12 parts of polyaspartic acid, 8-12 parts of glucolactone, 7-13 parts of potassium citrate, 2-8 parts of propyl gallate, 9-11 parts of sodium lactate, 7-13 parts of polylysine, 3-7 parts of polycyclohexanedicarboxylic acid and 5-15 parts of water. According to the biodegradable scale inhibitor provided by the invention, the scale inhibition performance, the dispersing performance, the thermal stability and the anti-shearing performance are further improved, the service life is prolonged, and meanwhile, good biodegradability and environmental friendliness are kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of scale inhibitors, and more particularly to a biodegradable phosphorus-free and nitrogen-free scale inhibitor. Background Art

[0002] With the rapid development of industry, water pollution is becoming increasingly serious, especially the scale problem in industrial equipment and pipelines, which not only affects the service life and efficiency of equipment, but also causes energy waste. Although traditional chemical scale inhibitors can effectively prevent the formation of scale, they are difficult to degrade themselves and will cause secondary pollution to the environment. Therefore, it is of great significance to develop an efficient, environmentally friendly and biodegradable scale inhibitor. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a biodegradable phosphorus-free and nitrogen-free scale inhibitor, comprising the following raw materials in parts by weight:

[0004] Chitosan grafted acrylic acid copolymer 25-35 parts, polyaspartic acid 8-12 parts, gluconolactone 8-12 parts, potassium citrate 7-13 parts, propyl gallate 2-8 parts, sodium lactate 9-11 parts, polylysine 7-13 parts, polycyclohexane dicarboxylic acid 3-7 parts, water 5-15 parts.

[0005] A biodegradable phosphorus-free and nitrogen-free scale inhibitor, comprising the following optimized raw materials in parts by weight:

[0006] 30 parts of chitosan grafted acrylic acid copolymer, 10 parts of polyaspartic acid, 10 parts of gluconolactone, 10 parts of potassium citrate, 5 parts of propyl gallate, 10 parts of sodium lactate, 10 parts of polylysine, 5 parts of polycyclohexanedicarboxylic acid, and 10 parts of water.

[0007] A biodegradable phosphorus-free and nitrogen-free scale inhibitor, comprising the following optimized raw materials in parts by weight:

[0008] Chitosan grafted acrylic acid copolymer 25 parts, polyaspartic acid 8 parts, gluconolactone 8 parts, potassium citrate 7 parts, propyl gallate 8 parts, sodium lactate 11 parts, polylysine 13 parts, polycyclohexane dicarboxylic acid 7 parts, water 15 parts.

[0009] A biodegradable phosphorus-free and nitrogen-free scale inhibitor, comprising the following optimized raw materials in parts by weight:

[0010] 35 parts of chitosan grafted acrylic acid copolymer, 12 parts of polyaspartic acid, 12 parts of gluconolactone, 13 parts of potassium citrate, 2 parts of propyl gallate, 9 parts of sodium lactate, 7 parts of polylysine, 3 parts of polycyclohexanedicarboxylic acid, and 5 parts of water.

[0011] A method for preparing a biodegradable phosphorus-free and nitrogen-free scale inhibitor comprises the following steps:

[0012] S1: Preparation of chitosan grafted acrylic acid copolymer;

[0013] Dissolve chitosan in dilute acetic acid solution, add initiator, raise the temperature to 50-70°C, slowly drop acrylic acid monomer, and react for 5-7 hours;

[0014] After the reaction is completed, the pH is adjusted to 7.0, and the mixture is precipitated, filtered, washed, and dried to obtain a chitosan-grafted acrylic acid copolymer.

[0015] S2: Preparation of polylysine and polyaspartic acid;

[0016] Lysine and aspartic acid were dissolved in sodium bicarbonate buffer respectively, and enzyme catalyst was added to react at 35-39°C for 24 hours. After the reaction was completed, small molecules were removed by dialysis, and polylysine and polyaspartic acid were obtained by freeze drying.

[0017] S3: Compounding of scale inhibitors;

[0018] According to the proportion, chitosan grafted acrylic acid copolymer, polylysine, polyaspartic acid, gluconolactone, propyl gallate, polycyclohexanedicarboxylic acid, potassium citrate and sodium lactate are dissolved in deionized water, stirred evenly, and the pH is adjusted to 7.0-8.0 to obtain a scale inhibitor solution.

[0019] S4: product preparation;

[0020] The antiscalant solution is spray dried or vacuum dried to obtain a solid powder product. Alternatively, the antiscalant solution is directly packaged to prepare a liquid product.

[0021] Preferably: in step S1, chitosan is dissolved in a dilute acetic acid solution, an initiator is added, the temperature is raised to 60°C, acrylic acid monomer is slowly added dropwise, and the reaction is carried out for 6 hours.

[0022] Preferably: in step S1, chitosan is dissolved in a dilute acetic acid solution, an initiator is added, the temperature is raised to 50°C, acrylic acid monomer is slowly added dropwise, and the reaction is carried out for 7 hours.

[0023] Preferably: in step S1, chitosan is dissolved in a dilute acetic acid solution, an initiator is added, the temperature is raised to 70°C, acrylic acid monomer is slowly added dropwise, and the reaction is carried out for 5 hours.

[0024] Preferably: in step S2, lysine and aspartic acid are dissolved in sodium bicarbonate buffer respectively, an enzyme catalyst is added, and the mixture is reacted at 37° C. for 24 hours.

[0025] Preferably: in step S4, the pH is adjusted to 7.5.

[0026] The beneficial effects of the present invention are as follows: the amino and carboxyl groups in the chitosan grafted acrylic acid copolymer of the present invention can form hydrogen bonds with the amino and carboxyl groups in polyaspartic acid, thereby enhancing the interaction between the scale inhibitor molecules and improving the scale inhibition and dispersion properties.

[0027] In addition to forming hydrogen bonds, the amino groups in polylysine can also form electrostatic interactions with the carboxyl groups in the chitosan-grafted acrylic acid copolymer, further enhancing the interaction between the scale inhibitor molecules and improving the scale inhibition and dispersion properties.

[0028] Both gluconolactone and propyl gallate contain lactone structures, which can form supramolecular structures through hydrophobicity and π-π stacking, thereby enhancing the thermal stability and high temperature resistance of the scale inhibitor. In addition to forming a supramolecular structure through hydrophobicity and π-π stacking, the phenolic hydroxyl group in propyl gallate can also form hydrogen bonds with the ester group in gluconolactone, thereby enhancing the thermal stability and high temperature resistance of the scale inhibitor.

[0029] Potassium citrate, sodium lactate and polycyclohexane dicarboxylic acid can produce a synergistic effect. In addition to the chelating and dispersing effects of potassium citrate and sodium lactate, the carboxyl group in polycyclohexane dicarboxylic acid can form a chelate with calcium and magnesium ions, and its hydrophobic cyclohexane structure can increase the dispersibility of the scale inhibitor in water, synergistically enhancing the scale inhibition performance. In addition, polycyclohexane dicarboxylic acid can also form a compound system with propyl gallate through hydrophobic action, further improving the comprehensive performance of the scale inhibitor.

[0030] Chitosan grafted acrylic acid copolymer, polyaspartic acid and polylysine can produce a synergistic effect. In addition to the original electrostatic effect, hydrogen bonding and chelation, the amino group in polylysine can also form an amide bond with the carboxyl group in polyaspartic acid, so that the three form a cross-linked network structure, which significantly enhances the structural stability and shear resistance of the scale inhibitor. At the same time, this cross-linked network structure can also encapsulate other functional components such as gluconolactone and propyl gallate through physical coating, so as to achieve the slow release and durability of the functional components and improve the service life of the scale inhibitor.

[0031] The biodegradable scale inhibitor proposed in the present invention further improves the scale inhibition performance, dispersion performance, thermal stability, shear resistance and service life, while maintaining good biodegradability and environmental friendliness. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is a scale inhibition performance test result diagram in Example 5 of the present invention;

[0033] Figure 2 is a graph showing the dispersion performance test results in Example 5 of the present invention;

[0034] Figure 3 This is a graph showing the Zeta potential test results in Example 6 of the present invention;

[0035] Figure 4 is a scale inhibition performance test result diagram in Example 6 of the present invention;

[0036] Figure 5 This is a graph showing the dispersion performance test results in Example 6 of the present invention;

[0037] Figure 6 is a DSC test result diagram in Example 7 of the present invention;

[0038] Figure 7 is a graph of TGA test results in Example 7 of the present invention;

[0039] Figure 8 This is a graph of the XRD test results in Example 7 of the present invention;

[0040] Fig. 9 is a scale inhibition performance test result diagram in Example 8 of the present invention;

[0041] Fig.10 This is a graph showing the dispersion performance test results in Example 8 of the present invention;

[0042] Fig.11 is a graph showing the thermal stability test results in Example 8 of the present invention;

[0043] Fig.12 This is a diagram showing the high temperature resistance test results in Example 8 of the present invention;

[0044] Fig.13 is a scale inhibition performance test result diagram in Example 9 of the present invention;

[0045] Fig.14 is a graph showing the dispersion performance test results in Example 9 of the present invention;

[0046] Fig.15 This is a DMA test result diagram in Example 9 of the present invention;

[0047] Fig.16 is a scale inhibition performance test result diagram in Example 10 of the present invention;

[0048] Fig.17 is a graph showing the dispersion performance test results in Example 10 of the present invention;

[0049] Fig.18 is a graph showing the thermal stability test results in Example 10 of the present invention;

[0050] Fig.19 is a graph showing the shear resistance test results in Example 10 of the present invention;

[0051] Fig. 20 is a graph showing the service life test results in Example 10 of the present invention;

[0052] Fig.21 is a graph showing the biodegradability test results in Example 10 of the present invention;

[0053] Fig. 22 is a graph showing the test results of calcium ion chelation capacity in Example 11 of the present invention;

[0054] Fig.23 This is a graph showing the test results of the magnesium ion chelation capacity in Example 10 of the present invention. DETAILED DESCRIPTION

[0055] The subject matter described herein will now be discussed with reference to example embodiments. It should be understood that the discussion of these embodiments is only to enable those skilled in the art to better understand and implement the subject matter described herein, and the functions and arrangements of the elements discussed may be changed without departing from the scope of protection of the contents of this specification. Each example may omit, replace or add various processes or components as needed. In addition, the features described relative to some examples may also be combined in other examples.

[0056] Example 1

[0057] In this embodiment, a biodegradable phosphorus-free and nitrogen-free scale inhibitor is proposed, which includes the following raw materials in parts by weight:

[0058] 30 parts of chitosan grafted acrylic acid copolymer, 10 parts of polyaspartic acid, 10 parts of gluconolactone, 10 parts of potassium citrate, 5 parts of propyl gallate, 10 parts of sodium lactate, 10 parts of polylysine, 5 parts of polycyclohexanedicarboxylic acid, and 10 parts of water.

[0059] Example 2

[0060] In this embodiment, a biodegradable phosphorus-free and nitrogen-free scale inhibitor is proposed, which includes the following raw materials in parts by weight:

[0061] Chitosan grafted acrylic acid copolymer 25 parts, polyaspartic acid 8 parts, gluconolactone 8 parts, potassium citrate 7 parts, propyl gallate 8 parts, sodium lactate 11 parts, polylysine 13 parts, polycyclohexane dicarboxylic acid 7 parts, water 15 parts.

[0062] Example 3

[0063] In this embodiment, a biodegradable phosphorus-free and nitrogen-free scale inhibitor is proposed, which includes the following raw materials in parts by weight:

[0064] 35 parts of chitosan grafted acrylic acid copolymer, 12 parts of polyaspartic acid, 12 parts of gluconolactone, 13 parts of potassium citrate, 2 parts of propyl gallate, 9 parts of sodium lactate, 7 parts of polylysine, 3 parts of polycyclohexanedicarboxylic acid, and 5 parts of water.

[0065] Example 4

[0066] In an embodiment of the present invention, a method for preparing a biodegradable phosphorus-free and nitrogen-free scale inhibitor is proposed, comprising the following steps:

[0067] S1: Preparation of chitosan grafted acrylic acid copolymer;

[0068] Chitosan is dissolved in a dilute acetic acid solution, an initiator is added, the temperature is raised to 50, 60 or 70° C., acrylic acid monomer is slowly added dropwise, and the reaction is carried out for 5, 6 or 7 hours; in this embodiment, the temperature is raised to 60° C. and the reaction is carried out for 6 hours.

[0069] After the reaction is completed, the pH is adjusted to 7.0, and the mixture is precipitated, filtered, washed, and dried to obtain a chitosan-grafted acrylic acid copolymer.

[0070] S2: Preparation of polylysine and polyaspartic acid;

[0071] Lysine and aspartic acid were dissolved in sodium bicarbonate buffer, enzyme catalyst was added, and the mixture was reacted at 35, 36, 37, 38 or 39°C for 24 hours. After the reaction was completed, small molecules were removed by dialysis, and polylysine and polyaspartic acid were obtained by freeze drying. In this embodiment, the mixture was reacted at 37°C for 24 hours.

[0072] S3: Compounding of scale inhibitors;

[0073] According to the proportion, chitosan grafted acrylic acid copolymer, polylysine, polyaspartic acid, gluconolactone, propyl gallate, polycyclohexanedicarboxylic acid, potassium citrate and sodium lactate are dissolved in deionized water, stirred evenly, and the pH is adjusted to 7.0, 7.5 or 8.0 to obtain a scale inhibitor solution. In this embodiment, the pH is adjusted to 7.5.

[0074] S4: product preparation;

[0075] The antiscalant solution is spray dried or vacuum dried to obtain a solid powder product. Alternatively, the antiscalant solution is directly packaged to prepare a liquid product.

[0076] Example 5

[0077] Chitosan grafted acrylic acid copolymer and polyaspartic acid both contain amino and carboxyl functional groups. When the two substances are mixed, intermolecular hydrogen bonds can be formed between the amino and carboxyl groups. Hydrogen bonds are a relatively strong intermolecular interaction force, and their formation mechanism is the electrostatic attraction between the hydrogen atoms in the amino or carboxyl groups and the electronegative atoms (such as oxygen atoms or nitrogen atoms) in another molecule.

[0078] In the mixed system of chitosan grafted acrylic acid copolymer and polyaspartic acid, the amino and carboxyl groups on the copolymer molecular chain can form intermolecular hydrogen bonds with the amino and carboxyl groups on the polyaspartic acid molecular chain, making the two substances tightly combined. This hydrogen bonding can enhance the interaction between the scale inhibitor molecules and increase the aggregation tendency of the scale inhibitor molecules in the solution, thereby more effectively preventing the formation and deposition of scale.

[0079] In addition, hydrogen bonding can also improve the dispersion performance of scale inhibitor molecules in the solution. Through the formation of hydrogen bonds, chitosan grafted acrylic acid copolymer and polyaspartic acid molecular chains are entangled with each other to form a composite similar to a mesh structure. This structure can increase the steric hindrance effect of scale inhibitor molecules in the solution, prevent molecular agglomeration and precipitation, and thus improve the dispersion performance and stability of scale inhibitors.

[0080] In this example, the effect of hydrogen bonding on the scale inhibition and dispersion properties in a mixed system of chitosan grafted acrylic acid copolymer and polyaspartic acid was studied to verify whether hydrogen bonding can significantly improve the performance of the scale inhibitor.

[0081] 1. Experimental Materials

[0082] Chitosan grafted acrylic acid copolymer (homemade, grafting degree 30%, molecular weight 50000).

[0083] Polyaspartic acid (purchased, molecular weight 10000).

[0084] Calcium carbonate (CaCO3, analytical grade).

[0085] Other reagents: sodium chloride, sodium hydroxide, hydrochloric acid, etc.

[0086] 2. Experimental Methods

[0087] A mixed solution of chitosan grafted acrylic acid copolymer and polyaspartic acid was prepared with a total concentration of 1000 mg / L and a mass ratio of the two components of 1:1, and the pH was adjusted to 7.0.

[0088] The static scale inhibition test method was used to evaluate the scale inhibition performance of the mixed solution. The test conditions were: temperature 80°C, pH 8.5, 200 mg / L CaCO3, stirring rate 100 rpm, and duration 10 hours.

[0089] The wet sieving method was used to test the dispersibility of the mixed solution. The test conditions were: temperature 25°C, pH 7.0, 10 g / LCaCO3, sieve aperture 0.045 mm, and vibration time 10 minutes.

[0090] A blank control group and a single component control group were set up to evaluate the effect of hydrogen bonding on performance.

[0091] 3. Experimental Results

[0092] See attached Figure 1 Table 1. The results of the scale inhibition performance test show that the scale inhibition rate of the mixed solution is significantly higher than that of a single component, indicating that hydrogen bonding can effectively improve the scale inhibition performance.

[0093] See attached Figure 2 Table 2. The dispersion performance test results show that the dispersion rate of the mixed solution is significantly higher than that of the single component, indicating that hydrogen bonding can significantly improve the dispersion performance.

[0094] 4. Experimental Results Analysis

[0095] The results of the scale inhibition test show that hydrogen bonding can significantly improve the scale inhibition performance of the scale inhibitor. This is because hydrogen bonding enhances the interaction between the molecules of the scale inhibitor, making the molecules easier to agglomerate, thereby more effectively preventing the formation and deposition of scale.

[0096] The dispersion test results show that hydrogen bonding can significantly improve the dispersion of antiscalant. This is because the formation of hydrogen bonding makes the antiscalant molecular chains entangled with each other to form a complex similar to a mesh structure, which increases the steric hindrance effect of the molecules and prevents molecular aggregation and precipitation.

[0097] Based on the test results of scale inhibition and dispersibility, it can be concluded that the hydrogen bonding effect in the mixed system of chitosan grafted acrylic acid copolymer and polyaspartic acid can significantly improve the scale inhibition and dispersibility of the scale inhibitor, verifying the important role of hydrogen bonding in improving the performance of scale inhibitors.

[0098] Example 6

[0099] Polylysine is a cationic polymer with primary amino functional groups in its side chains. Under appropriate pH conditions of the solution, the primary amino groups can be protonated to form positively charged ammonium salt structures (-NH3 + On the other hand, the carboxyl groups (-COOH) in the chitosan-grafted acrylic acid copolymer will ionize in the solution to form negatively charged carboxylate ions (-COO - ).

[0100] When polylysine and chitosan grafted acrylic acid copolymer are mixed, electrostatic attraction will occur between the protonated primary amino group and the ionized carboxyl group to form an ion pair or salt bridge structure. This electrostatic interaction can further enhance the interaction between the antiscalant molecules, making the molecular chains tightly combined to form a more stable complex.

[0101] The mechanism of improving scale inhibition and dispersion performance by electrostatic interaction is as follows:

[0102] Scale inhibition performance: electrostatic interaction makes the molecular chains of scale inhibitors tightly combined to form a denser adsorption layer, which can more effectively prevent the formation and deposition of scale crystals. In addition, electrostatic interaction can also enhance the binding force between scale inhibitor molecules and the surface of scale crystals, further inhibiting the growth of scale.

[0103] Dispersion performance: Electrostatic interaction makes the molecular chains of the scale inhibitor form a cross-linked network structure, which increases the steric hindrance effect of the molecules. This structure can effectively disperse the scale crystals and prevent them from agglomerating and precipitating, thereby improving the dispersion performance and stability of the scale inhibitor.

[0104] This example studies the effect of electrostatic interaction on the scale inhibition and dispersion performance in a mixed system of polylysine and chitosan grafted acrylic acid copolymer, and verifies whether electrostatic interaction can significantly improve the performance of the scale inhibitor.

[0105] 1. Experimental Materials

[0106] Chitosan grafted acrylic acid copolymer (homemade, grafting degree 30%, molecular weight 50000)

[0107] Poly-lysine (purchased, molecular weight 5000)

[0108] Calcium carbonate (CaCO3, analytical grade)

[0109] Other reagents: sodium chloride, sodium hydroxide, hydrochloric acid, etc.

[0110] 2. Experimental Methods

[0111] A mixed solution of chitosan grafted acrylic acid copolymer and polylysine was prepared with a total concentration of 1000 mg / L and a molar ratio of the two components of 1:1. The pH was adjusted to 6.0 (the optimal pH for the protonation of polylysine).

[0112] The Zeta potential of the mixed solution was tested using a Zeta potential analyzer to evaluate the electrostatic interaction in the system.

[0113] The static scale inhibition test method was used to evaluate the scale inhibition performance of the mixed solution. The test conditions were: temperature 80°C, pH 8.5, 200 mg / L CaCO3, stirring rate 100 rpm, and duration 10 hours.

[0114] The wet sieving method was used to test the dispersibility of the mixed solution. The test conditions were: temperature 25°C, pH 7.0, 10 g / LCaCO3, sieve aperture 0.045 mm, and vibration time 10 minutes.

[0115] A blank control group and a single component control group were set up to evaluate the effect of electrostatic interaction on performance.

[0116] 3. Experimental Results

[0117] See attached Figure 3 Table 3. The Zeta potential test results show that the Zeta potential of the mixed solution is between the two single components, and the absolute value is significantly reduced, indicating that there is an electrostatic interaction in the system and an electrically neutral complex is formed.

[0118] See attached Figure 4 Table 4. The results of the scale inhibition performance test show that the scale inhibition rate of the mixed solution is significantly higher than that of a single component, indicating that electrostatic interaction can effectively improve the scale inhibition performance.

[0119] See attached Figure 5 Table 5. The dispersion performance test results show that the dispersion rate of the mixed solution is significantly higher than that of the single component, indicating that electrostatic interaction can significantly improve the dispersion performance.

[0120] 4. Experimental Results Analysis

[0121] Zeta potential test confirmed the existence of electrostatic interaction in the mixed system of poly-lysine and chitosan grafted acrylic acid copolymer, forming an electrically neutral complex.

[0122] The results of the antiscaling performance test show that electrostatic interaction can significantly improve the antiscaling performance of the antiscalant. This is because electrostatic interaction strengthens the interaction between antiscalant molecules, making the molecular chains tightly combined to form a denser adsorption layer, thereby more effectively preventing the formation and deposition of scale.

[0123] The dispersion test results show that electrostatic interaction can significantly improve the dispersion performance of the scale inhibitor. This is because electrostatic interaction allows the molecular chains of the scale inhibitor to form a cross-linked network structure, which increases the steric hindrance effect of the molecules, effectively disperses the scale crystals, and prevents their aggregation and precipitation.

[0124] Based on the test results of Zeta potential, scale inhibition performance and dispersion performance, it can be concluded that the electrostatic interaction in the mixed system of polylysine and chitosan grafted acrylic acid copolymer can significantly improve the scale inhibition performance and dispersion performance of the scale inhibitor, verifying the important role of electrostatic interaction in improving the performance of scale inhibitors.

[0125] Example 7

[0126] Both gluconolactone and propyl gallate are compounds containing lactone structures. Lactone is a cyclic ester structure formed by the condensation of carboxyl and ortho-hydroxyl groups, and has strong hydrophobicity and rigidity. When gluconolactone and propyl gallate are mixed, their lactone structures can form a supramolecular structure through hydrophobic interaction and π-π stacking.

[0127] Hydrophobic interaction refers to the mutual attraction between non-polar groups, which is an important intermolecular force. The alkyl and aromatic groups in the lactone structure are hydrophobic groups, which can gather together through hydrophobic interaction to form a hydrophobic region.

[0128] π-π stacking refers to the face-to-face arrangement between aromatic rings, which is a special intermolecular force. Propyl gallate contains the trihydroxybenzene ring structure of gallic acid and is an aromatic ring compound. When propyl gallate molecules aggregate, the benzene rings can form an orderly face-to-face arrangement through π-π stacking.

[0129] The synergistic effect of hydrophobicity and π-π stacking can make gluconolactone and propyl gallate form a stable supramolecular structure. This supramolecular structure can enhance the thermal stability and high temperature resistance of the scale inhibitor for the following reasons:

[0130] The supramolecular structure forms a tight physical cross-linking network between the antiscalant molecules, improving the rigidity and heat resistance of the material.

[0131] The formation of hydrophobic areas can hinder the penetration of water molecules and other small molecules, reducing the degradation and decomposition of antiscalants at high temperatures.

[0132] The π-π stacking effect causes the aromatic rings to form an orderly arrangement, increasing the crystallinity and thermal stability of the antiscalant molecules.

[0133] In addition to the hydrophobic effect and π-π stacking effect, the phenolic hydroxyl group in propyl gallate can also form intermolecular hydrogen bonds with the ester group in gluconolactone. Hydrogen bonds are a strong intermolecular force that can further enhance the stability of the supramolecular structure and improve the high temperature resistance of the scale inhibitor.

[0134] This example studies the effect of the supramolecular effect of gluconolactone and propyl gallate on the thermal stability and high temperature resistance of the scale inhibitor, and verifies whether the supramolecular effect can significantly improve the heat resistance of the scale inhibitor.

[0135] 1. Experimental Materials

[0136] Gluconolactone (purchased, purity ≥98%).

[0137] Propyl gallate (purchased, purity ≥ 95%).

[0138] Chitosan grafted acrylic acid copolymer (homemade, grafting degree 30%, molecular weight 50000).

[0139] Other reagents: sodium chloride, sodium hydroxide, hydrochloric acid, etc.

[0140] 2. Experimental Methods

[0141] A mixed solution of gluconolactone and propyl gallate was prepared with a total concentration of 1000 mg / L and a molar ratio of the two components of 1:1.

[0142] The mixed solution was mixed with chitosan grafted acrylic acid copolymer in a mass ratio of 9:1 to prepare a scale inhibitor sample.

[0143] Differential scanning calorimetry (DSC) was used to test the thermal stability of the antiscalant samples. The test conditions were: nitrogen atmosphere, heating rate 10°C / min, and temperature range 30-500°C.

[0144] Thermogravimetric analysis (TGA) was used to test the high temperature resistance of the antiscalant samples. The test conditions were: nitrogen atmosphere, heating rate 10°C / min, temperature range 30-800°C.

[0145] X-ray diffraction analysis (XRD) was used to characterize the crystallinity of the antiscalant sample. The test conditions were: Cu Kα radiation, 2θ range 5-60°, and scanning speed 5° / min.

[0146] A blank control group (pure chitosan grafted acrylic acid copolymer) and a single component control group were set up to evaluate the effect of supramolecular action on performance.

[0147] 3. Experimental Results

[0148] See also Figure 6 Table 6. The DSC test results show that the glass transition temperature and thermal decomposition temperature of the mixed antiscalant are significantly higher than those of the blank control group and the single component, indicating that the supramolecular effect improves the thermal stability of the antiscalant.

[0149] See also Figure 7 Table 7. The TGA test results show that the weight loss temperature of the mixed antiscalant is significantly higher than that of the blank control group and the single component, indicating that the supramolecular effect improves the high temperature resistance of the antiscalant.

[0150] See also Figure 8 Table 8. The XRD test results show that the crystallinity of the mixed antiscalant is significantly higher than that of the blank control group and the single component, indicating that the supramolecular effect increases the crystallinity of the antiscalant and improves its thermal stability.

[0151] 4. Experimental Results Analysis

[0152] The results of DSC and TGA tests show that the supramolecular effect of gluconolactone and propyl gallate can significantly improve the thermal stability and high temperature resistance of the scale inhibitor. This is because the supramolecular structure enhances the interaction between the scale inhibitor molecules, forms a tight physical cross-linking network, and improves the rigidity and heat resistance of the material.

[0153] XRD test results show that supramolecular action can improve the crystallinity of the scale inhibitor, which is due to the π-π stacking effect that makes the aromatic rings form an orderly arrangement, increasing the regularity and crystallization tendency of the molecules. The increase in crystallinity further improves the thermal stability of the scale inhibitor.

[0154] Based on the test results of DSC, TGA and XRD, it can be concluded that the supramolecular effects of gluconolactone and propyl gallate, including hydrophobic effect, π-π stacking effect and hydrogen bonding effect, can significantly improve the thermal stability and high temperature resistance of the scale inhibitor, verifying the important role of supramolecular effect in improving the performance of scale inhibitors.

[0155] Example 8

[0156] Potassium citrate, sodium lactate and polycyclohexane dicarboxylic acid are all compounds containing carboxyl groups. They can produce a synergistic effect in scale inhibitors and improve scale inhibition performance.

[0157] First of all, potassium citrate and sodium lactate are commonly used chelating agents and dispersants. The carboxyl groups in them can form stable chelates with calcium and magnesium ions in water, thereby inhibiting the crystallization and deposition of calcium and magnesium ions. At the same time, potassium citrate and sodium lactate also have good dispersibility and can be adsorbed on the surface of scale crystals to prevent the aggregation and growth of scale crystals.

[0158] Polycyclohexanedicarboxylic acid is a dicarboxyl compound, in which the two carboxyl groups can form more stable chelates with calcium and magnesium ions, further enhancing the scale inhibition effect. In addition, polycyclohexanedicarboxylic acid contains a hydrophobic cyclohexane structure, which can increase the dispersibility of scale inhibitor molecules in water and prevent molecular agglomeration and precipitation. The introduction of hydrophobic groups also helps the adsorption of scale inhibitor molecules on the solid-liquid interface to form a denser protective layer.

[0159] The synergistic effect of potassium citrate, sodium lactate and polycyclohexane dicarboxylic acid can enhance the scale inhibition performance in the following aspects:

[0160] The synergistic effect of multiple chelating groups improves the chelating ability and chelating stability of calcium and magnesium ions.

[0161] The introduction of hydrophobic groups increases the dispersibility of antiscalant molecules in water and their adsorption at the solid-liquid interface.

[0162] The combination of different types of antiscalant molecules forms a multi-synergistic antiscaling system, which improves the breadth and applicability of the antiscaling effect.

[0163] In addition, polycyclohexanedicarboxylic acid can also form a compound system with propyl gallate through hydrophobic interaction. Propyl gallate contains hydrophobic aromatic rings and ester groups, which can interact hydrophobically with the cyclohexane groups in polycyclohexanedicarboxylic acid to form a more stable supramolecular structure. This compound system can further improve the thermal stability, high temperature resistance and shear resistance of the scale inhibitor, and also help to improve the comprehensive performance and synergistic effect of the scale inhibitor.

[0164] This example studies the synergistic scale inhibition effect of potassium citrate, sodium lactate and polycyclohexane dicarboxylic acid, and evaluates the influence of different components on the scale inhibition performance.

[0165] The compounding effect of polycyclohexanedicarboxylic acid and propyl gallate was studied, and the influence of the compounding system on the comprehensive performance of the scale inhibitor was evaluated.

[0166] 1. Experimental Materials

[0167] Potassium citrate (purchased, purity ≥ 99%).

[0168] Sodium lactate (purchased, purity ≥ 98%).

[0169] Polycyclohexanedicarboxylic acid (purchased, molecular weight 1000).

[0170] Propyl gallate (purchased, purity ≥ 95%).

[0171] Chitosan grafted acrylic acid copolymer (homemade, grafting degree 30%, molecular weight 50000).

[0172] Calcium carbonate (CaCO3, analytical grade).

[0173] Other reagents: sodium chloride, sodium hydroxide, hydrochloric acid, etc.

[0174] 2. Experimental Methods

[0175] A mixed solution of potassium citrate, sodium lactate and polycyclohexane dicarboxylic acid was prepared with a total concentration of 1000 mg / L and a molar ratio of the three components of 1:1:1.

[0176] The mixed solution was mixed with chitosan grafted acrylic acid copolymer in a mass ratio of 9:1 to prepare a scale inhibitor sample.

[0177] A composite solution of polycyclohexanedicarboxylic acid and propyl gallate was prepared with a total concentration of 1000 mg / L and a molar ratio of the two components of 1:1.

[0178] The compound solution was mixed with chitosan grafted acrylic acid copolymer in a mass ratio of 9:1 to prepare a compound scale inhibitor sample.

[0179] The static scale inhibition test method was used to evaluate the scale inhibition performance of different scale inhibitor samples. The test conditions were: temperature 80°C, pH 8.5, 200 mg / L CaCO3, stirring rate 100 rpm, and duration 10 hours.

[0180] The wet sieving method was used to test the dispersion performance of different scale inhibitor samples. The test conditions were: temperature 25°C, pH 7.0, 10g / LCaCO3, sieve aperture 0.045mm, and vibration time 10 minutes.

[0181] Differential scanning calorimetry (DSC) was used to test the thermal stability of the compound antiscalant sample. The test conditions were: nitrogen atmosphere, heating rate 10°C / min, and temperature range 30-500°C.

[0182] Thermogravimetric analysis (TGA) was used to test the high temperature resistance of the compound antiscalant sample. The test conditions were: nitrogen atmosphere, heating rate 10°C / min, temperature range 30-800°C.

[0183] A blank control group and a single component control group were set up to evaluate the effects of synergistic effects and compound effects on performance.

[0184] 3. Experimental Results

[0185] See also Fig. 9 Table 9 in Fig.10 Table 10, Fig.11 Table 11 in Fig.12 Table 12 in .

[0186] 4. Experimental Results Analysis

[0187] The results of the scale inhibition performance test show that the mixed system of potassium citrate, sodium lactate and polycyclohexane dicarboxylic acid has a significant synergistic scale inhibition effect, and the scale inhibition rate is much higher than that of a single component. This is because the synergistic effect of multiple chelating groups improves the chelating ability of calcium and magnesium ions, while the hydrophobic groups increase the dispersibility of the scale inhibitor molecules in water and the adsorption at the solid-liquid interface.

[0188] The dispersion performance test results show that the mixed system of potassium citrate, sodium lactate and polycyclohexane dicarboxylic acid has excellent dispersion effect, and the dispersion rate is significantly higher than that of a single component. This is due to the improved dispersion of scale inhibitor molecules in water and the adsorption on the surface of scale crystals.

[0189] The results of thermal stability and high temperature resistance test show that the compound system of polycyclohexanedicarboxylic acid and propyl gallate has higher thermal stability and high temperature resistance, and the glass transition temperature, thermal decomposition temperature and weight loss temperature are significantly improved. This is because the hydrophobic-hydrophobic interaction forms a more stable supramolecular structure, which enhances the heat resistance and anti-degradation ability of the scale inhibitor molecule.

[0190] Based on the test results of scale inhibition, dispersion, thermal stability and high temperature resistance, it can be concluded that potassium citrate, sodium lactate and polycyclohexanedicarboxylic acid have significant synergistic scale inhibition effect, and the compounding effect of polycyclohexanedicarboxylic acid and propyl gallate can further improve the comprehensive performance of the scale inhibitor.

[0191] Example 9

[0192] Chitosan grafted acrylic acid copolymer, polyaspartic acid and polylysine are all functional polymers containing amino and carboxyl groups. They can produce multiple synergistic effects in scale inhibitors and improve the performance and stability of scale inhibitors.

[0193] First, the amino and carboxyl groups in the chitosan grafted acrylic acid copolymer can form intermolecular hydrogen bonds and electrostatic interactions with the amino and carboxyl groups in polyaspartic acid and polylysine, thereby enhancing the interaction between the antiscalant molecules. At the same time, these functional groups can also form stable chelates with calcium and magnesium ions in water, thereby improving the chelating ability and antiscaling performance of the antiscalant.

[0194] In addition to these effects, the amino group in polylysine can also undergo condensation reaction with the carboxyl group in polyaspartic acid to form an amide bond. Amide bonds are a type of covalent bond that is more stable and strong than hydrogen bonds and electrostatic interactions. Through the formation of amide bonds, chitosan grafted acrylic acid copolymer, polyaspartic acid and polylysine can be cross-linked into a network structure. This cross-linked network structure has the following advantages:

[0195] The structural stability and shear resistance of the scale inhibitor are significantly improved. The cross-linked network structure forms a strong chemical bond between the scale inhibitor molecules, preventing the sliding and breaking of the molecular chain and improving the mechanical strength and tolerance of the material.

[0196] A large number of micropores and gaps are formed in the cross-linked network structure, which can be used to encapsulate other functional components such as gluconolactone and propyl gallate through physical encapsulation. These functional components can be protected and fixed in the cross-linked network structure to avoid their leakage and loss.

[0197] The functional components are encapsulated in the cross-linked network structure, which can achieve slow release and lasting effect. When the scale inhibitor is added to the water, the cross-linked network structure can control the release rate of the functional components, making it work for a longer time, thus improving the service life and persistence of the scale inhibitor.

[0198] The cross-linked network structure can also improve the thermal stability and high temperature resistance of the scale inhibitor. Chemical cross-linking improves the heat resistance and anti-degradation ability of the material, allowing the scale inhibitor to be used at higher temperatures and has a wider range of applications.

[0199] This example studies the synergistic scale inhibition effect of chitosan grafted acrylic acid copolymer, polyaspartic acid and polylysine, and evaluates the influence of different components on the scale inhibition performance.

[0200] The mechanism of chitosan grafted acrylic acid copolymer, polyaspartic acid and polylysine forming a cross-linked network structure was studied, and the effect of the cross-linked network structure on the performance of scale inhibitors was evaluated.

[0201] 1. Experimental Materials

[0202] Chitosan grafted acrylic acid copolymer (homemade, grafting degree 30%, molecular weight 50000).

[0203] Polyaspartic acid (purchased, molecular weight 10000).

[0204] Poly-lysine (purchased, molecular weight 5000).

[0205] Gluconolactone (purchased, purity ≥98%).

[0206] Propyl gallate (purchased, purity ≥ 95%).

[0207] Calcium carbonate (CaCO3, analytical grade)

[0208] Other reagents: sodium chloride, sodium hydroxide, hydrochloric acid, thionyl chloride, etc.

[0209] 2. Experimental Methods

[0210] A mixed solution of chitosan grafted acrylic acid copolymer, polyaspartic acid and polylysine was prepared with a total concentration of 1000 mg / L and a molar ratio of the three components of 1:1:1.

[0211] Thionyl chloride was added to the mixed solution, the pH value was adjusted to 8.0, and the mixture was reacted at room temperature for 24 hours to prepare a cross-linked scale inhibitor sample.

[0212] A mixed solution of gluconolactone and propyl gallate was prepared with a total concentration of 1000 mg / L and a molar ratio of the two components of 1:1.

[0213] The mixed solution of gluconolactone and propyl gallate was mixed with the cross-linked scale inhibitor sample in a mass ratio of 9:1 to prepare a coated scale inhibitor sample.

[0214] The static scale inhibition test method was used to evaluate the scale inhibition performance of different scale inhibitor samples. The test conditions were: temperature 80°C, pH 8.5, 200 mg / L CaCO3, stirring rate 100 rpm, and duration 10 hours.

[0215] Dynamic mechanical analysis (DMA) was used to test the storage modulus and loss factor of the cross-linked antiscalant sample and evaluate the shear resistance of the material.

[0216] A blank control group and a single component control group were set up to evaluate the synergistic effect and the influence of the cross-linked network structure on the performance.

[0217] IV. Experimental Results

[0218] See See Fig.13 Table 13, Fig.14 Table 14, Fig.15 Table 15 in .

[0219] 4. Experimental Results Analysis

[0220] The results of the scale inhibition and dispersion performance tests show that chitosan grafted acrylic acid copolymer, polyaspartic acid and polylysine have significant synergistic scale inhibition effects, and the combination of the three can greatly improve the scale inhibition rate and dispersion rate. The performance of the cross-linked scale inhibitor and the coated scale inhibitor is further improved, confirming the promotion effect of the cross-linked network structure and functional component coating on the scale inhibition performance.

[0221] The DMA test results show that the cross-linked network structure significantly improves the shear resistance and structural stability of the scale inhibitor, which is due to the inhibitory effect of chemical cross-linking on molecular chain sliding and breaking.

[0222] Example 10

[0223] This example evaluates the advantages of the biodegradable scale inhibitor of the present invention in terms of scale inhibition performance, dispersion performance, thermal stability, shear resistance, service life and biodegradability through comparative tests with similar scale inhibitors, thereby verifying the effectiveness and environmental friendliness of the present invention.

[0224] 1. Experimental Materials

[0225] The biodegradable scale inhibitor in Example 1 (prepared according to the method in Example 4).

[0226] Commercial chemical antiscalant A (purchased).

[0227] Commercial chemical antiscalant B (purchased).

[0228] Commercial environmentally friendly antiscalant C (purchased).

[0229] Calcium carbonate (CaCO3, analytical grade).

[0230] Other reagents: sodium chloride, sodium hydroxide, hydrochloric acid, etc.

[0231] 2. Experimental Methods

[0232] The static scale inhibition test method was used to evaluate the scale inhibition performance of different scale inhibitors. The test conditions were: temperature 80°C, pH 8.5, 200 mg / L CaCO3, stirring rate 100 rpm, and duration 10 hours.

[0233] The wet sieving method was used to test the dispersion performance of different scale inhibitors. The test conditions were: temperature 25°C, pH 7.0, 10g / LCaCO3, sieve aperture 0.045mm, and vibration time 10 minutes.

[0234] Differential scanning calorimetry (DSC) was used to test the thermal stability of different scale inhibitors. The test conditions were: nitrogen atmosphere, heating rate 10°C / min, and temperature range 30-500°C.

[0235] The shear resistance of different scale inhibitors was tested using a rotational rheometer. The test conditions were: temperature 25°C, shear rate range 0.1-100s-1.

[0236] The service life of different scale inhibitors was evaluated by continuous dosing test. The test conditions were: temperature 80℃, pH 8.5, 200mg / L CaCO3, scale inhibitor concentration 10mg / L, continuous dosing for 30 days, and scale inhibition rate was measured every day.

[0237] The biochemical oxygen demand (BOD) test was used to evaluate the biodegradability of different scale inhibitors. The test conditions were: temperature 25°C, dissolved oxygen ≥ 2 mg / L, activated sludge inoculation, and BOD value was measured for 28 days.

[0238] IV. Experimental Results

[0239] See See Fig.16 Table 16, Fig.17 Table 17, Fig.18 Table 18, Fig.19 Table 19, Fig. 20 Table 20, Fig.21 Table 21 in .

[0240] 4. Experimental Results Analysis

[0241] The test results of scale inhibition and dispersion performance show that the scale inhibition rate and dispersion rate of the optimized biodegradable scale inhibitor are better than those of commercial chemical scale inhibitors and environmentally friendly scale inhibitors, confirming that the formula optimization can significantly improve the scale inhibition performance.

[0242] The results of the thermal stability test showed that the thermal decomposition temperature of the optimized biodegradable scale inhibitor was significantly higher than that of other scale inhibitors, indicating that it has better high temperature resistance and thermal stability.

[0243] The results of the anti-shear performance test showed that the apparent viscosity decrease rate of the optimized biodegradable scale inhibitor was the lowest, confirming its excellent anti-shear performance and mechanical stability.

[0244] The service life test results show that the optimized biodegradable scale inhibitor maintains a high scale inhibition rate during long-term continuous use, confirming its good persistence and service life.

[0245] The results of biodegradability tests showed that the biodegradation rate of the optimized biodegradable scale inhibitor was much higher than that of commercial chemical scale inhibitors and slightly higher than that of commercial environmentally friendly scale inhibitors, confirming its excellent environmental friendliness and biodegradability.

[0246] Embodiment 11

[0247] In this example, the chelating capacity test was performed to evaluate the chelating ability of the biodegradable scale inhibitor of the present invention on calcium and magnesium ions, and the results were compared with similar scale inhibitors to verify the effect of the present invention on the chelating performance.

[0248] 1. Experimental Materials

[0249] The biodegradable scale inhibitor of the present invention (prepared according to the method in Example 4).

[0250] Commercial chemical antiscalant A (purchased).

[0251] Commercial chemical antiscalant B (purchased).

[0252] Commercial environmentally friendly antiscalant C (purchased).

[0253] Calcium chloride (CaCl2, analytical grade).

[0254] Magnesium chloride (MgCl2, analytical grade).

[0255] EDTA standard solution (0.01 mol / L).

[0256] Indicator: Chrome black T, calcium red.

[0257] 2. Experimental Methods

[0258] Prepare 200 mg / L antiscalant solution and adjust the pH to 8.5.

[0259] Prepare 500 mg / L CaCl2 and MgCl2 solutions respectively.

[0260] Take 25mL of antiscalant solution and place it in a conical flask, add 25mL of CaCl2 or MgCl2 solution and mix well.

[0261] Add 2-3 drops of indicator (chrome black T for calcium ions, calcium red for magnesium ions) to the solution.

[0262] Titrate with 0.01 mol / L EDTA standard solution until the solution color changes and record the amount of EDTA used.

[0263] The chelating capacity of the scale inhibitor for calcium and magnesium ions (mmol / g) was calculated based on the amount of EDTA used.

[0264] Repeat steps 3-6, measure each sample 3 times in parallel, and take the average value.

[0265] 3. Experimental Results

[0266] See also Fig. 22 The calcium ion chelation capacity test results and Fig.23 The magnesium ion chelation capacity test results.

[0267] 4. Experimental Results Analysis

[0268] The test results of calcium ion chelation capacity show that the biodegradable scale inhibitor of the present invention has the highest chelation capacity for calcium ions, reaching 6.28 mmol / g, which is significantly higher than commercial chemical scale inhibitors and environmentally friendly scale inhibitors, confirming its excellent calcium chelation ability.

[0269] The test results of magnesium ion chelation capacity show that the biodegradable scale inhibitor of the present invention has the highest chelation capacity for magnesium ions, reaching 5.86 mmol / g, which is significantly higher than other scale inhibitors, indicating that it has stronger magnesium chelation ability.

[0270] The reason why the biodegradable scale inhibitor of the present invention exhibits a higher chelating capacity can be attributed to the synergistic effect of various chelating functional groups in the formula, such as carboxyl, hydroxyl, amino, etc., as well as the molecular structure and spatial configuration, which jointly promote the chelating and coordination effect between the scale inhibitor molecules and calcium and magnesium ions.

[0271] The chelation capacity test experiment confirmed that the biodegradable scale inhibitor of the present invention has excellent calcium and magnesium chelation performance, and its chelation capacity is significantly higher than similar commercial chemical scale inhibitors and environmentally friendly scale inhibitors. This result further verifies the effectiveness of the present invention, indicating that the scale inhibitor can more effectively inhibit the formation and deposition of calcium and magnesium scale, and has obvious advantages in scale inhibition performance.

[0272] The above describes an embodiment of the present embodiment, but the present embodiment is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the guidance of the present embodiment, ordinary technicians in this field can also make many forms, all of which are within the protection of the present embodiment.

Claims

1. A biodegradable phosphorus-free and nitrogen-free scale inhibitor, characterized in that: The composition comprises the following raw materials in parts by weight: Chitosan grafted acrylic acid copolymer 25-35 parts, polyaspartic acid 8-12 parts, gluconolactone 8-12 parts, potassium citrate 7-13 parts, propyl gallate 2-8 parts, sodium lactate 9-11 parts, polylysine 7-13 parts, polycyclohexane dicarboxylic acid 3-7 parts, water 5-15 parts.

2. A biodegradable phosphorus-free and nitrogen-free scale inhibitor according to claim 1, characterized in that: The composition comprises the following raw materials in parts by weight: 30 parts of chitosan grafted acrylic acid copolymer, 10 parts of polyaspartic acid, 10 parts of gluconolactone, 10 parts of potassium citrate, 5 parts of propyl gallate, 10 parts of sodium lactate, 10 parts of polylysine, 5 parts of polycyclohexanedicarboxylic acid, and 10 parts of water.

3. The biodegradable phosphorus-free and nitrogen-free scale inhibitor according to claim 1, characterized in that: The composition comprises the following raw materials in parts by weight: Chitosan grafted acrylic acid copolymer 25 parts, polyaspartic acid 8 parts, gluconolactone 8 parts, potassium citrate 7 parts, propyl gallate 8 parts, sodium lactate 11 parts, polylysine 13 parts, polycyclohexane dicarboxylic acid 7 parts, water 15 parts.

4. The biodegradable phosphorus-free and nitrogen-free scale inhibitor according to claim 1, characterized in that: The composition comprises the following raw materials in parts by weight: 35 parts of chitosan grafted acrylic acid copolymer, 12 parts of polyaspartic acid, 12 parts of gluconolactone, 13 parts of potassium citrate, 2 parts of propyl gallate, 9 parts of sodium lactate, 7 parts of polylysine, 3 parts of polycyclohexanedicarboxylic acid, and 5 parts of water.

5. The biodegradable phosphorus-free and nitrogen-free scale inhibitor according to claim 1, characterized in that: The preparation method of the scale inhibitor comprises the following steps: S1: Preparation of chitosan grafted acrylic acid copolymer; Dissolve chitosan in dilute acetic acid solution, add initiator, raise the temperature to 50-70°C, slowly drop acrylic acid monomer, and react for 5-7 hours; After the reaction is completed, the pH is adjusted to 7.0, and the mixture is precipitated, filtered, washed, and dried to obtain a chitosan-grafted acrylic acid copolymer. S2: Preparation of polylysine and polyaspartic acid; Lysine and aspartic acid were dissolved in sodium bicarbonate buffer respectively, and enzyme catalyst was added to react at 35-39°C for 24 hours. After the reaction was completed, small molecules were removed by dialysis, and polylysine and polyaspartic acid were obtained by freeze drying. S3: Compounding of scale inhibitors; According to the proportion, chitosan grafted acrylic acid copolymer, polylysine, polyaspartic acid, gluconolactone, propyl gallate, polycyclohexanedicarboxylic acid, potassium citrate and sodium lactate are dissolved in deionized water, stirred evenly, and the pH is adjusted to 7.0-8.0 to obtain a scale inhibitor solution. S4: product preparation; The antiscalant solution is spray dried or vacuum dried to obtain a solid powder product. Alternatively, the antiscalant solution is directly packaged to prepare a liquid product.

6. The biodegradable phosphorus-free and nitrogen-free scale inhibitor according to claim 5, characterized in that: In step S1, chitosan is dissolved in a dilute acetic acid solution, an initiator is added, the temperature is raised to 60°C, acrylic acid monomer is slowly added dropwise, and the reaction is carried out for 6 hours.

7. The biodegradable phosphorus-free and nitrogen-free scale inhibitor according to claim 5, characterized in that: In step S1, chitosan is dissolved in a dilute acetic acid solution, an initiator is added, the temperature is raised to 50°C, acrylic acid monomer is slowly added dropwise, and the reaction is carried out for 7 hours.

8. The biodegradable phosphorus-free and nitrogen-free scale inhibitor according to claim 5, characterized in that: In step S1, chitosan is dissolved in a dilute acetic acid solution, an initiator is added, the temperature is raised to 70°C, acrylic acid monomer is slowly added dropwise, and the reaction is carried out for 5 hours.

9. The biodegradable phosphorus-free and nitrogen-free scale inhibitor according to claim 5, characterized in that: In step S2, lysine and aspartic acid are dissolved in sodium bicarbonate buffer, respectively, and an enzyme catalyst is added to react at 37° C. for 24 hours.

10. The biodegradable phosphorus-free and nitrogen-free scale inhibitor according to claim 5, characterized in that: In step S4, the pH is adjusted to 7.5.

Citation Information

Patent Citations

  • Biodegradable non-phosphorous anti-scale corrosion inhibitor and preparation method thereof

    CN102774969A

  • Chitosan grafted hyperbranched polymer polyamide-amine (PAMAM), and preparation method and application thereof

    CN105037736A

  • Reverse osmosis membrane composite anti-scaling bactericide

    CN105597550A

  • Preparation method of phosphorus-free nitrogen-free environment-friendly scale-inhibiting dispersing agent

    CN107935207A

  • Circulating water scale inhibitor

    CN115651267A